2020
DOI: 10.1371/journal.pone.0232971
|View full text |Cite
|
Sign up to set email alerts
|

Changing social inequalities in smoking, obesity and cause-specific mortality: Cross-national comparisons using compass typology

Abstract: Background In many countries smoking rates have declined and obesity rates have increased, and social inequalities in each have varied over time. At the same time, mortality has declined in most high-income countries, but gaps by educational qualification persist-at least partially due to differential smoking and obesity distributions. This study uses a compass typology to simultaneously examine the magnitude and trends in educational inequalities across multiple countries in: a) smoking and obesity; b) smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(57 reference statements)
1
8
1
Order By: Relevance
“… 5 , 25 , 26 Many studies do not report RIIs, despite this being the recommended method for international comparisons. 6 However, our RIIs were generally higher than those reported for those aged 35-79 years in European countries covering the period from 1990s to the early 2000s and for New Zealand in the period 2006-11, 4 , 28 although direct comparisons remain difficult given that previously reported RIIs are generally not age stratified. The fact that the relative inequality estimates observed in this study are generally larger than observed in comparable countries may reflect, at least in part, a greater concentration of disadvantage among those with lower levels of education in Australia 29 , 30 and/or larger socioeconomic differences in risk factors in Australia compared with other countries (e.g.…”
Section: Discussioncontrasting
confidence: 55%
“… 5 , 25 , 26 Many studies do not report RIIs, despite this being the recommended method for international comparisons. 6 However, our RIIs were generally higher than those reported for those aged 35-79 years in European countries covering the period from 1990s to the early 2000s and for New Zealand in the period 2006-11, 4 , 28 although direct comparisons remain difficult given that previously reported RIIs are generally not age stratified. The fact that the relative inequality estimates observed in this study are generally larger than observed in comparable countries may reflect, at least in part, a greater concentration of disadvantage among those with lower levels of education in Australia 29 , 30 and/or larger socioeconomic differences in risk factors in Australia compared with other countries (e.g.…”
Section: Discussioncontrasting
confidence: 55%
“…The score for each question varied according to the frequency of symptoms, from zero (no day) to three (almost every day), which generates a maximum score of 27. The sum of items allows for grading between no depression (0-4), mild depression (5)(6)(7)(8)(9), moderate depression (10)(11)(12)(13)(14), moderately severe depression (15)(16)(17)(18)(19) and severe depression (20-27) 16 . Individuals with ten or more points were considered "with depression".…”
Section: Methodsmentioning
confidence: 99%
“…The association of health-related behaviors with chronic diseases and early mortality is widely recognized 1,2 , and an increase in social inequalities in mortality 3,4 and in health-related behaviors has been detected in recent decades 5,6 . These findings highlight the need to better understand the role of health behaviors in increasing inequalities in morbidity and mortality 7 and draws attention to the importance of the quality of the health programs implemented to prevent unhealthy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The control measures implemented tend to reach more affluent segments of the population in a first step, which can lead to an increase in inequalities 13 . To reduce health inequalities, tobacco control must focus essentially on vulnerable segments of society 16 .…”
Section: Smokingmentioning
confidence: 99%
“…Despite reductions in several unhealthy behaviors, studies have suggested an increase in social inequality in the prevalence of these behaviors in many countries 15,16 . In recent decades, several developed countries have registered an increase in inequalities in mortality among socioeconomic strata 17 .…”
Section: Introductionmentioning
confidence: 99%